Implementation of a risk-stratified approach to prevent postoperative nausea and vomiting in an institution with high baseline rates of prophylaxis - Kadhiresan R Murugappan; Mario Moric; Xuanji Wang; Jessica Kruse; Ariel Mueller; Myles D Boone; Cristina Barboi (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Although a risk-adjusted approach to preventing postoperative nausea and vomiting (PONV) is generally recommended, the successful implementation of such practice without mandated protocols remains elusive. To date, such a strategy has never been adapted to curb high baseline rates of prophylaxis. Material and Methods: We conducted an observational study on a cohort of patients undergoing elective surgery before and after the implementation of a quality improvement initiative including a risk-stratified approach to prevent PONV. The primary outcome was the number of prophylactic interventions administered. Secondary outcome included the repetition of ineffective medications and the need for rescue medication in the post-anesthesia care unit (PACU). Results: A total of 636 patients were included; 325 patients during the control period and 311 after the intervention. The educational program failed to reduce the amount of prophylactic antiemetics administered (2.0 vs. 2.6, P < 0.001) and the repeat administration of ineffective medications for rescue (16% vs. 20%, P = 0.15). More patients in the intervention group required rescue medication compared to the control group (16.9% vs. 9.7%; P = 0.04). Conclusion: Implementation of best practices to combat PONV remains elusive. Our results indicate that difficulties in changing provider behavior also apply to institutions with high prophylactic antiemetic administration rates.